Emission Mechanisms of Si Nanocrystals and Defects in SiO2 Materials. (26th August 2014) - Rodríguez, José Antonio; Vásquez-Agustín, Marco Antonio; Morales-Sánchez, Alfredo; Aceves-Mijares, Mariano
Abstract : Motivated by the necessity to have all silicon optoelectronic circuits, researchers around the world are working with light emitting silicon materials. Such materials are silicon dielectric compounds with silicon content altered, such as silicon oxide or nitride, enriched in different ways with Silicon. Silicon Rich Oxide or silicon dioxide enriched with silicon, and silicon rich nitride are without a doubt the most promising materials to reach this goal. Even though they are subjected to countless studies, the light emission phenomenon has not been completely clarified. So, a review of different proposals presented to understand the light emission phenomenon including emissions related to nanocrystals and to point defects in SiO2 is presented.